Regarding the pushing progress of Terazzo sample confirmation - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the pushing progress of Terrazzo sample confirmation for BRACU new campus project.